2019
DOI: 10.1111/php.13128
|View full text |Cite
|
Sign up to set email alerts
|

pH and Charge Effects Behind the Interaction of Artepillin C, the Major Component of Green Propolis, With Amphiphilic Aggregates: Optical Absorption and Fluorescence Spectroscopy Studies

Abstract: Brazilian green propolis is one of the bee products most consumed in the world to prevent diseases, owing antioxidant, antimicrobial, anti‐inflammatory and antitumor activities. The major component of Brazilian green propolis is Artepillin C (ArtC), a cinnamic acid derivative with two prenylated groups that improve the affinity of the compound for lipophilic environment. Here, we have employed optical absorption and fluorescence techniques to draw conclusions on how ArtC interacts with amphiphilic aggregates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The literature supports the notion that Artepillin C favors a neutral state as pH decreases [17]. Beyond 50 µM, molecules tend to aggregate due to their limited water solubility, augmenting interactions with lipophilic domains, such as the cell plasma membrane, and subsequently intensifying cytotoxic effects [18,22,34]. Notably, the decline in cellular viability observed at pH values of 6.8, 6.5, and 6.0 when cells were exposed to Artepillin C concentrations exceeding 50 µM, marked by significant differentiation from the respective pH controls, clearly underscores the pH-dependent effect.…”
Section: Cell Viability Studiesmentioning
confidence: 55%
See 2 more Smart Citations
“…The literature supports the notion that Artepillin C favors a neutral state as pH decreases [17]. Beyond 50 µM, molecules tend to aggregate due to their limited water solubility, augmenting interactions with lipophilic domains, such as the cell plasma membrane, and subsequently intensifying cytotoxic effects [18,22,34]. Notably, the decline in cellular viability observed at pH values of 6.8, 6.5, and 6.0 when cells were exposed to Artepillin C concentrations exceeding 50 µM, marked by significant differentiation from the respective pH controls, clearly underscores the pH-dependent effect.…”
Section: Cell Viability Studiesmentioning
confidence: 55%
“…Interestingly, this metabolic shift persists regardless of molecular oxygen levels in cancer cells, leading to a substantial elevation in lactate production-up to 40 times higher compared to healthy cells [21]. A previous study showed that models mimicking healthy and tumor cell membranes exhibit distinct responses based on lipid composition and media pH [18,22]. Under physiological conditions (pH 7.4), Artepillin C exhibits an affinity for the lipid assembly without perturbing the structural integrity of the lipid membrane.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The optical absorption spectra represented the state of protonation dictated by the local pH on the surface of micelles and lipid vesicles (20). Useful data were obtained for the optimization of postharvest photochemical protocols for the valorization of cabbage waste using a nondestructive optical sensor (21).…”
Section: Introductionmentioning
confidence: 99%